Analysis of European mobility surveys and their potential to support studies on the impact of electric vehicles on energy and infrastructure needs in Europe - Paşaoğlu, Guzay; Zubaryeva, Alyona; Fiorello, Davide; Thiel, Christian (Elsevier BV, 2014)
Projections show that CO2 emissions from road transport will continue to rise in the future if adequate policy measures are not implemented. Electrically driven vehicle (EDV) deployment is one way to reduce the CO2 emissions. EDV drive and charge patterns determine the resulting electricity demand, emission reductions, future infrastructure requirements and the integration of non-dispatchable renewable electricity. In order to analyse the impact of EDVs on European energy and infrastructure needs, the driving patterns of potential EDV users should be analysed. Due to the lack of sufficient historical representative data on driving patterns with EDVs, this study analyses whether European national travel surveys (NTS) can be a potential data source to derive usage patterns for EDVs. We perform a meta-analysis of NTS from 9 European countries to assess their adequacy for analysing the impacts of EDVs on the European electricity system. Several gaps in data availability and comparability are identified. Except for the UK, European NTS are not detailed enough to assess EDV charging profiles, which is also due to the methodological differences used for NTS data collection in the various countries. We conclude that a dedicated survey needs to be developed to reliably estimate EDV charging profiles.